The Canonical and the Dynamic: A Model for Understanding Artistic Change in the 18th Dynasty - Wong, Jun Yi (Zeitschrift für ägyptische Sprache und Altertumskunde, 2023)
The 18 th Dynasty of Egypt saw the introduction of various new artistic elements often described as ‘expressive’ or ‘naturalistic’. This development appears to have occurred within a short time span, and many of its details remain unclear. This article examines this phenomenon with particular focus on palace decorations from Tell el-Dab’a, Malqata and Amarna. The three sites display many artistic commonalities, despite the changes in temple decoration that occurred within the same period. It is proposed that this discrepancy reflects two separate strands of artistic development, namely (i) a canonical style predominantly found in religious and funerary contexts; and (ii) a ‘dynamic’ style that is epitomised by the palace decorations. Analyses are made regarding the development of the dynamic style, its influence on Amarna art, as well as the mechanism of its transmission.